The EAEU and the problems of development of integration (on the example of Kazakhstan and Belarus) - Yurova, N.V.; Perova, N.S. (BUKETOV BUSINESS REVIEW, 2019)
In the article the theoretical aspect of such concepts as integration, economic integration, international integration is discussed. The main economic indicators of interaction of the Republic of Kazakhstan and the Republic of Belarus in the framework of the integration are reviewed. The data on the export and import of the main types of goods to the Republic of Kazakhstan and the Republic of Belarus are studied in detail. The main groups of export-import goods for 2018 are singled out, and the dynamics in comparison with 2017 is analyzed. It is noted that the main import strategic goods from Republic of Kazakhstan are oil and oil products, and from the Republic of Belarus to the Republic of Kazakhstan — dairy products and milk products. The narrow sides of this cooperation are revealed. Ways of improvement of economic cooperation between the countries are offered that is almost significant element of a research.